Ventana de siembra de Vicia villosa en intercultivo con caña de azúcar - Martinez Calsina, Luciana; Saez, Julio Victor; Fontana, Paola Daniela; Felipe, Arturo; Zerrizuela, Sol Constanza; Gallac, Marcelo Javier; Perez Gomez, Sergio Gregorio; Vallejo, Juan Inosencio; Acreche, Martin Moises; Erazzu, Luis Ernesto (INTA y Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2025)
Poster